2021
DOI: 10.1016/j.bioflm.2021.100057
|View full text |Cite
|
Sign up to set email alerts
|

Microbial fuel cells and their electrified biofilms

Abstract: Bioelectrochemical systems (BES) represent a wide range of different biofilm-based bioreactors that includes microbial fuel cells (MFCs), microbial electrolysis cells (MECs) and microbial desalination cells (MDCs). The first described bioelectrical bioreactor is the Microbial Fuel Cell and with the exception of MDCs, it is the only type of BES that actually produces harvestable amounts of electricity, rather than requiring an electrical input to function. For these reasons, this review article, with previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 130 publications
1
37
0
Order By: Relevance
“…15 At the phylum level (Figure 7A), Proteobacteria, Bacteroidetes, and Spirochaetes were abundantly enriched contributing to approximately $70.0% community. The aforementioned phyla are promising electricity producers 62,63 with Proteobacteria identified as possible exoelectrogen. 64 On the class level (Figure 7B), Deltaproteobacteria (24%) and Betaproteobacteria (11%) from phylum Proteobacteria were dominant, followed by Bacteroidia (12%) belonging to Bacteroidetes.…”
Section: Microbial Community Analysismentioning
confidence: 99%
“…15 At the phylum level (Figure 7A), Proteobacteria, Bacteroidetes, and Spirochaetes were abundantly enriched contributing to approximately $70.0% community. The aforementioned phyla are promising electricity producers 62,63 with Proteobacteria identified as possible exoelectrogen. 64 On the class level (Figure 7B), Deltaproteobacteria (24%) and Betaproteobacteria (11%) from phylum Proteobacteria were dominant, followed by Bacteroidia (12%) belonging to Bacteroidetes.…”
Section: Microbial Community Analysismentioning
confidence: 99%
“…Differing from batteries, in microbial fuel cells there is a start‐up process whereby bacteria will form a biofilm on the anode and this formation of biofilm has a direct influence on the performance. [ 162 ] Ye et al combined a microchannel reactor based on transparent ITO and phase contrast microscopy to visualize biofilm formation under various anolyte flow rates (Figure 12g). They found that at moderate flow rates, superior electrochemical performance was obtained (Figure 12h).…”
Section: Applications Of Microfluidic Energy Storage and Release Systemsmentioning
confidence: 99%
“…[ 72 ], Pseudomonas aeruginosa [ 73 ], and B. subtilis [ 74 ]. Applications of engineered biofilms include manufacturing aquaplastics [ 75 ], minimizing fouling on reverse-osmosis membranes [ 76 ], and producing electricity in microbial fuel cells [ 77 , 78 ]. Controlling and optimizing the production of biofilms provides a foundation for further development of ELMs.…”
Section: Applicationsmentioning
confidence: 99%